Tissue response to impact loading in sports - Brüggemann, G. P.; Niehoff, A . (ISBS - Conference Proceedings Archive (Konstanz), 2011)
The response of biological tissue to impact like mechanical loading in sports is of vital interest in sports biomechanics, athletic training research and especially the development of an injury reduction model. Bone and articular cartilage react differently to mechanical loading in the long term. A strong association to the loading patterns for the response of bone but not for that of cartilage has been be identified. For the short term experimental results provide evidence on two different articular cartilage responses related to loading regimes (high frequent impact vs. low frequent impact). From the reported results the risk of overuse through impact loading was derived as a function of sports related impact loading patterns and subject specific prerequisites.